Development of Laser Beam Diffraction Technique for Determination of Thermal Expansion Coefficient of Polymeric Thin Films - Thuan, Nguyen Van; Son, Tran Vinh; Trung, Tran Quang; Thao, Tran Thi; Dinh, Nguyen Nang (VNU Journal of Science: Mathematics - Physics; Vol 31 No 2, 2015)
Laser beam diffraction by a patterned surface has been investigated theoretically and experimentally for the determination of the thermal expansion coefficient (a) of polymeric materials. By tracking the deviation of the first order diffraction mode from surface-patterned polymers, expansion coefficients in a range 10 -7 to 10 -4 K -1 can be measured by temperature changes less than 100 o C. A set-up of laser diffraction (SLD) was made, using a He-Ne laser (l = 632.8 nm) and thin film casting technique. The results of measurements on the SLD system for polymers like PVK polycarbonate, PDMS, organic complex (chitosan) and conducting polymer (P3HT) showed that SLD technique can be applied to determine thermal expansion coefficients of different polymeric materials with a considerably small volume. Especially, the fact that a of P3HT-composite films was found to be much lower than that of the pure P3HT suggests a potential application of polymeric composites for organic devices working at elevated temperature, for organic solar cells (OSC) in particular. Keywords: Laser beam diffraction; thermal expansion; diffraction grating; polymer.